2015
DOI: 10.1038/srep14418
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of C-phycocyanin effect on astrocytes-mediated neuroprotection against oxidative brain injury using 2D and 3D astrocyte tissue model

Abstract: Drugs are currently being developed to attenuate oxidative stress as a treatment for brain injuries. C-phycocyanin (C-Pc) is an antioxidant protein of green microalgae known to exert neuroprotective effects against oxidative brain injury. Astrocytes, which compose many portions of the brain, exert various functions to overcome oxidative stress; however, little is known about how C-Pc mediates the antioxidative effects of astrocytes. In this study, we revealed that C-Pc intranasal administration to the middle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 53 publications
0
32
0
1
Order By: Relevance
“…GSH-Px, GSH, and SOD, indicators of the rate and extent of oxidative stress, could provide first line of protection from ischemic cerebral injury [ 48 ]. EA induced neuroprotection against cerebral ischemia through reducing oxidative stress, which may provide new mechanisms [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSH-Px, GSH, and SOD, indicators of the rate and extent of oxidative stress, could provide first line of protection from ischemic cerebral injury [ 48 ]. EA induced neuroprotection against cerebral ischemia through reducing oxidative stress, which may provide new mechanisms [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among all neurotrophic factors, BDNF is the best-studied in depression, which exerts its effects through two specific receptors, tyrosine kinase receptor (Trk)B and p75. The activation of TrkB facilitates neuronal survival, differentiation and synaptogenesis [13,14], whereas p75 triggers apoptosis [15,16]. Therefore, anti-inflammatory/modulating neurotrophins may provide new strategy for the future prevention and treatment in depression.…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes were isolated from rat brains by primary cell culture. Sprague-Dawley rats (1 day old) were used as the experimental animals based on the previous study [20]. Briefly, brain meninges and hippocampuses were removed from the cortical part of the rat brain, after which the cortical brain was pulverized using a Pasteur pipette.…”
Section: Cell Culture Of Primary Astrocytesmentioning
confidence: 99%
“…In a previous study, 5,11-dideoxy TTX was reported to be isolated with standard TTX from puffer fish [18]. It was also reported that TTX derivatives were toxic in an in vivo animal study, although with less toxicity than standard TTX [20]. Acetonitrile and water were used as the mobile phases.…”
Section: Fractionation Of Small Molecules Through Hplcmentioning
confidence: 99%